MODERN INNOVATIVE DIRECTIONS AND TOOLS FOR MANAGING THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN THE AIC SYSTEM OF UKRAINE (INNOVATIVE ECONOMY, 2024)
Kuprina N.M. MODERN INNOVATIVE DIRECTIONS AND TOOLS FOR MANAGING THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN THE AIC SYSTEM OF UKRAINEPurpose. The purpose of the article is to reveal and propose directions for the economic transformation of agricultural enterprises and to substantiate certain management tools for its implementation to ensure the effectiveness of their functioning, competitiveness and development of activities in the AIC system of Ukraine.Methodology of the research. The following research methods were used to achieve the set goal: method of structural and logical analysis – when forming the structure and logic of the article; the method of analytical and comparative analysis to substantiate the strategic importance of the activities of agricultural enterprises in the AIC system, research and formation of tools for analysis, evaluation and control of the persistent transformation of the activities of agricultural enterprises and its necessity, the conceptual and categorical apparatus of the theory of the national economy (in particular, the concepts of "economic transformation", "persistent transformation"), research into types of strategic analysis of the macro-environment of the object; tabular and graphic – for a visual representation of conducting a strategic analysis according to the McKinsey method and the formation of types and tools for the persistent transformation of research objects.Findings. It was proved that agro-food products became the main export product in Ukraine in 2022 during military operations, produced by agricultural enterprises and the food industry. It is substantiated that their activities have both economic and strategic importance for any country and ensure both economic and food security, and are a source of production of strategically important products that significantly affect other countries at the macroeconomic and global levels. The need to find innovative ways to ensure the functioning of agricultural enterprises - persistent transformation of their activity, and the use of tools for its implementation to manage the effectiveness of activity, development and ensure competitiveness in modern conditions is substantiated.Originality. A methodical approach to assessing the need for persistent transformation of the activities of agricultural enterprises in the agro-industrial complex system at the macro- and meso-levels of research, based on a strategic analysis that takes into account the full cycle (from the production of raw materials to the processing and sale of products) on the basis of the McKinsey method, received further development. The use of a system of tools for the analysis, evaluation and control of the persistent transformation of agricultural enterprises in the agro-industrial complex system in accordance with the functions of managing their activities was formed and substantiated.Practical value. Proposals substantiated by the results of research can be used by authorities, auditing and consulting firms, institutions of higher education and business structures to ensure the efficiency of functioning, competitiveness and development of agricultural enterprises in the agro-industrial complex system of the region and the country.Key words: agricultural enterprises, agro-industrial complex, economic transformation, persistence of activity, innovative tools, ensuring competitiveness, efficiency of functioning, development of activity.
Keywords: agricultural enterprises; agro-industrial complex; economic transformation; persistence of activity; innovative tools; ensuring competitiveness; efficiency of functioning; development of activity.